Transradial Neuroendovascular Procedures in Adolescents: Initial Single-Center Experience - Alshehri, H.; Dmytriw, A.A.; Bhatia, K.; Bickford, S.; Rea, V.; Shkumat, N.; Muthusami, P. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: The feasibility and safety of transradial angiography is not established outside the adult literature. The objective of this study was to assess the feasibility and safety of transradial access for neuroangiography in adolescents.MATERIALS AND METHODS: A retrospective case-control study was performed, comparing transradial neuroendovascular procedures in adolescents (age range, 10–18 years) with an age- and procedure-matched cohort of transfemoral neuroendovascular procedures. Clinical and procedural details, including type of procedure, conversion rate, fluoroscopy time, radiation dose, complications, and readmissions, were reported by descriptive statistics or measures of central tendency and compared using a t test or nonparametric equivalent. A P value < .05 was considered statistically significant.RESULTS: Twenty adolescents (mean age, 14.6 [SD, 1.7] years, M/F ratio = 9:11) who underwent transradial neuroangiography were compared against 20 adolescents (mean age, 14.4 [SD, 2.1 ] years, M/F ratio = 12:8) who underwent transfemoral neuroangiography. We found no significant difference in procedural success (0% conversion rate), fluoroscopy times (33.7 [SD, 40.2] minutes versus 23.3 [SD, 26.2] minutes, P = .34) and radiation dose (150.9 [SD, 133.7] Gy×cm2 and 122.9 [SD, 79.7] Gy×cm,2 P = .43) There were 2 self-limiting postprocedural complications in the transradial group. There were no major hemorrhages, need for further interventions, or readmissions in either group.CONCLUSIONS: The benefits of transradial angiography described for adults can likely be safely extended to adolescents. These are important data before transitioning to smaller children and should be prospectively evaluated in a larger cohort.